Die Stimmen der Eroberten bei Ermoldus Nigellus. Eine Mahnung an Ludwig den Frommen und Pippin von Aquitanien - Foerster, Anne (Eroberte im Mittelalter: Umbruchssituationen erleben, bewältigen, gestalten)

Review on: Christos Tsakas: Post-war Greco-German Relations, 1953-1981. Economic Development, Business Interests and European Integration, Basingstoke 2022. - Schönhärl, Korinna (Sehepunkte)

ABHÄNGEN - Ein- und Ausgrenzen, Kanonisieren, Kollaborieren in Pop, Kunst und Medien. - Jacke, Christoph (Impulse. Texte und Bilder zur Kunstvermittlung.)

Editorial. - Jacke, Christoph; Autsch, Sabine; Pickartz, Tim (Impulse. Texte und Bilder zur Kunstvermittlung.)

Scaffolding the human partner by contrastive guidance in an explanatory human-robot dialogue - Groß, A.; Singh, Amit; Banh, Ngoc Chi; Richter, B.; Scharlau, Ingrid; Rohlfing, Katharina J.; Wrede, B. (Frontiers in Robotics and AI)
Explanation has been identified as an important capability for AI-based systems, but research on systematic strategies for achieving understanding in interaction with such systems is still sparse. Negation is a linguistic strategy that is often used in explanations. It creates a contrast space between the affirmed and the negated item that enriches explaining processes with additional contextual information. While negation in human speech has been shown to lead to higher processing costs and worse task performance in terms of recall or action execution when used in isolation, it can decrease processing costs when used in context. So far, it has not been considered as a guiding strategy for explanations in human-robot interaction. We conducted an empirical study to investigate the use of negation as a guiding strategy in explanatory human-robot dialogue, in which a virtual robot explains tasks and possible actions to a human explainee to solve them in terms of gestures on a touchscreen. Our results show that negation vs. affirmation 1) increases processing costs measured as reaction time and 2) increases several aspects of task performance. While there was no significant effect of negation on the number of initially correctly executed gestures, we found a significantly lower number of attempts—measured as breaks in the finger movement data before the correct gesture was carried out—when being instructed through a negation. We further found that the gestures significantly resembled the presented prototype gesture more following an instruction with a negation as opposed to an affirmation. Also, the participants rated the benefit of contrastive vs. affirmative explanations significantly higher. Repeating the instructions decreased the effects of negation, yielding similar processing costs and task performance measures for negation and affirmation after several iterations. We discuss our results with respect to possible effects of negation on linguistic processing of explanations and limitations of our study.
Keywords: HRI; XAI; negation; understanding; explaining; touch interaction; gesture

When Did Europe Become Identified With Christianity? The Revolutionary Origins of an All Too Common Slogan - Süßmann, Johannes (Beyond Binaries. Religious Diversity in Europe)

Ibn Khaldûn and the Political Economy of Communication: A Reply to Graham Murdock - Fuchs, Christian (Critical Sociology)

Conjunctive and additive group work reduce academic procrastination: insights from a vignette study - Koppenborg, Markus; Klingsieck, Katrin B.; Hüffmeier, Joachim (Current Psychology)
Abstract Group work can increase individual effort, performance, and positive affect, if group members perceive their own contribution as indispensable for the group product. A vignette methodology was applied to investigate whether group work may also reduce procrastination. The vignettes described a typical academic assignment, while varying the task structure (individual work vs. conjunctive group work vs. additive group work) and group member ability (high vs. low). For each vignette, student participants ( N = 443) provided ratings on their perceived indispensability, procrastination of the assignment, and affect. When group member ability was high, procrastination was lower in additive group work as compared to individual work. When group member ability was low, procrastination was lower in conjunctive group work as compared to both individual work and additive group work. As predicted, perceived indispensability mediated the difference in procrastination between conjunctive and additive group work. Moderation analyses further revealed that the effects were more pronounced for high trait procrastinators. Further, both types of group work led to increases in task-related positive affect as compared to individual work. By demonstrating the relevance of group work as a social factor, the results should be useful for the extension of existing programs targeting procrastination, and may inspire measures for preventing procrastination by changes in the study environment.
Keywords: General Psychology

GEProS - Entwicklung und Evaluation einer digitalen Simulation zur Förderung diagnostischer Kompetenz von Lehramtsstudierenden - Grotegut, Lea
Um Schüler*innenmerkmale korrekt zu beurteilen benötigen Lehrkräfte diagnostische Kompetenz. Insbesondere die genaue Einschätzung nicht-kognitiver Merkmale von Schüler*innen fällt Lehrkräften eher schwer. Dazu zählen auch mögliche Anzeichen für Lern- und Verhaltensauffälligkeiten. Maßnahmen zur Förderung diagnostischer Kompetenz fokussieren bisher größtenteils die Diagnostik fachspezifischer, situativer Urteilsgegenstände, wie Fehlkonzepte im Mathematikunterricht. Systematisch evaluierte Fördermaßnahmen, die das Erkennen und Beurteilen von Lern- und Verhaltensauffälligkeiten bei Schüler*innen fokussieren, existieren bisher nicht.Aus diesem Anlass wurde die digitale, problemorientierte Simulation GEProS zur Förderung diagnostischer Kompetenz von Lehramtsstudierenden entwickelt und systematisch in drei längsschnittlichen, (quasi-)experimentellen Kontrollgruppenstudien evaluiert. Die Ergebnisse zeigen, dass die GEProS einen Mehrwert für die Förderung diagnostischer Kompetenz insbesondere im Bereich selbstbestimmter Motivation bieten kann. Ein integriertes Quiz mit Feedback kann mittels testing effect darüber hinaus der Erwerb deklarativ-konzeptionellen Wissens als zentrale Disposition diagnostischer Kompetenz in GEProS unterstützen. Die Ergebnisse tragen durch das entwickelte Integrative Modell diagnostischer Kompetenz zur Theoriebildung sowie zur Forschung und Entwicklung im Bereich der Förderung diagnostischer Kompetenz bei, indem eine Maßnahme zur Förderung diagnostischer Kompetenz für einen fächerübergreifenden, zeitlich stabilen Urteilsgegenstand systematisch evaluiert wurde. Durch die Ableitung und Berücksichtigung wesentlicher Merkmale digitaler Simulationen trägt diese Arbeit außerdem zur theoretischen Fundierung digitaler Simulationen bei.

Kompetenzentwicklung in der Lehrkräftebildung: der Mehrwert einer digitalen Simulation - Grotegut, Lea; Klingsieck, Katrin B. (ZeHf – Zeitschrift für empirische Hochschulforschung)
Die Förderung diagnostischer Kompetenz in der Lehrer*innenbildung birgt zwei Herausforderungen: Erstens bleibt in großen Lehrveranstaltungen wenig Raum für die notwendige Anwendung theoretischen Wissens, zweitens können Fehlentscheidungen in realen diagnostischen Situationen gravierende negative Folgen für Schüler*innen haben. Eine digitale Simulation kann beiden Herausforderungen begegnen. In diesem Beitrag wurde eine digitale, problemorientierte Simulation zur Förderung diagnostischer Kompetenz von Lehramtsstudierenden evaluiert und mit einer textbasierten, problemorientierten und einer lehrendenzentrierten Kontrollgruppe verglichen. Die Ergebnisse zeigen positive Effekte für die digitale Simulation hinsichtlich der selbstbestimmten Motivation, aber einen geringeren Wissenszuwachs im Vergleich zum lehrendenzentrierten Setting. Die Selbstwirksamkeit nahm in allen drei Gruppen zu. Eine digitale Simulation bietet in der untersuchten Form somit einen, wenn auch geringen, Mehrwert für die Lehrkräftebildung im Bereich der Kompetenzentwicklung.
Keywords: General Earth and Planetary Sciences; General Engineering; General Environmental Science